Risk Mitigation in Newsvendor Networks: Resource Diversification, Flexibility, Sharing, and Hedging - Van Mieghem, Jan A. (Management Science, 2007)
This paper studies how judicious resource allocation in networks mitigates risk. Theory is presented for general utility functions and mean-variance formulations and is illustrated with networks featuring resource diversification, flexibility (e.g., inventory substitution), and sharing (commonality). In contrast to single-resource settings, risk-averse newsvendors may invest more in networks than risk-neutral newsvendors: some resources and even total spending may exceed risk-neutral levels. With normally distributed demand, risk-averse newsvendors change resource levels roughly proportionally to demand variance, while risk-neutral agents adjust only proportionally to standard deviation. Two effects explain this operational hedge and suggest rules of thumb for strategic placement of safety capacity and inventory in networks: (1) Risk pooling suggests rebalancing capacity toward inexpensive resources that serve lower-profit variance markets. This highlights the role of profit variance (instead of demand variance) in risk-averse network investment. (2) Ex post revenue maximization suggests rebalancing capacity toward substitutable flexible but away from shared capacity when markets differ in profitability. Capacity imbalance and allocation flexibility thus mitigate profit risk and truly are operational hedges.